2010
DOI: 10.1159/000284401
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Cell Products: Authenticity, Identity, Genomic Stability and Status of Differentiation

Abstract: Cellular therapies that either use modifications of a patient’s own cells or allogeneic cell lines are becoming in vogue. Besides the technical issues of optimal isolation, cultivation and modification, quality control of the generated cellular products are increasingly being considered to be more important. This is not only relevant for the cell’s therapeutic application but also for cell science in general. Recent changes in editorial policies of respected journals, which now require proof of authenticity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Cell culture is widely used in biomedical science such as vaccine production, cell biology, carcinogenic cell studies, study of chemical compounds and drugs eff ects in specifi c cells, biological products synthesis, among others (Rojas et al 2008;Capes-Davis et al 2010;Dittmar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell culture is widely used in biomedical science such as vaccine production, cell biology, carcinogenic cell studies, study of chemical compounds and drugs eff ects in specifi c cells, biological products synthesis, among others (Rojas et al 2008;Capes-Davis et al 2010;Dittmar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Karyotype is a method used to identify specifi c chromosome markers, the genus and species of the animal, to analyze the characteristic chromosome number of each species and also determine common aneuploid in cell lines (Markovic & Markovic 1998;Wenger et al 2005, Ramya 2009Dittmar et al 2010;Leandro & Cruz 2012). It's a method that takes more time and depends on an expert ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety of these cells has to be guaranteed upon their administration as immunocompromised patients might have an increased risk of tumour induction or the potential risk of stimulating the growth of a previously undetected cancer. The risk of tumorigenicity and genomic instability remains an obstacle for any given stem-cell based therapy product and will have to be adequately assessed prior to approval for human use (Dittmar, Simann et al 2010). In this respect, the first clinical trials have been undertaken to assess the safety of MSC administration and potential treatment options for GvHD and it has been reported that autologous and allogeneic MSCs are safe to be injected in patients with life threatening acute GvHD not responding to conventional immunosuppressive therapy without acute toxicity and no signs of ectopic tissue formation (Lazarus, Koc et al 2005).…”
Section: Quality Considerations and Regulations In Msc Based Therapymentioning
confidence: 99%
“…Dittmar et al [1] address the identity crisis currently becoming visible with the use of available cell lines: 20-30% of the cell lines in use are not the cell lines we think they are. This hypothesis is recently being supported by a paper of Boonstra et al [2] and commented on in an editorial by Shoemaker [3].…”
mentioning
confidence: 99%